Village Fund Management in Improving Community Welfare in Socio-Economic Sector - Dian Afrianita (International Journal on Social Science, Economics and Art, 2019)
The objective of the research was to find out and to describe the management of Village Funds in improving people’s welfare in socio-economic field and to find out people’s contribution. The research used qualitative method with descriptive study design. It was conducted at Sei Sentosa Village, Panai Hulu Subdistrict, Labuhanbatu Regency. The samples were 10 respondents, taken by using purposive sampling technique. The data were gathered by conducting observation, in-depth interviews, and documentary study. The result of the research showed that the management of DD (village funds) was aimed to improve the villagers’ welfare in the socio-economic field which included the priority to use DD for constructing road and ditch infrastructure and the stages applied in the management of DD. The implementation principle was transparent, self-management, and fairness. The stages which had to be done were planning, budgeting, implementing, and supervising. People’s contribution to managing DD was by providing ideas, manpower, and property.